The Ocean and Cryosphere in a Changing Climate Special Report of the Intergovernmental Panel on Climate Change - Panel on Climate Change, Intergovernmental (Physical Sciences, 2022)
This IPCC Special Report provides the latest comprehensive assessment of the ocean and cryosphere in a changing climate. It serves policymakers, decision makers, stakeholders, and all interested parties with unbiased, up-to-date, policy-relevant information. This title is also available as Open Access on Cambridge Core.